Simulating CXCR5 Dynamics in Complex Tissue Microenvironments - Cosgrove, Jason; Alden, Kieran; Stein, Jens V.; Coles, Mark C.; Timmis, Jon (Frontiers in Immunology, 2021)
To effectively navigate complex tissue microenvironments, immune cells sense molecular concentration gradients using G-protein coupled receptors. However, due to the complexity of receptor activity, and the multimodal nature of chemokine gradients in vivo, chemokine receptor activity in situ is poorly understood. To address this issue, we apply a modelling and simulation approach that permits analysis of the spatiotemporal dynamics of CXCR5 expression within an in silico B-follicle with single-cell resolution. Using this approach, we show that that in silico B-cell scanning is robust to changes in receptor numbers and changes in individual kinetic rates of receptor activity, but sensitive to global perturbations where multiple parameters are altered simultaneously. Through multi-objective optimization analysis we find that the rapid modulation of CXCR5 activity through receptor desensitization and recycling on the cell surface is required for optimal antigen scanning rates. From these analyses we predict that the chemokine receptor signaling dynamics regulate migration in complex tissue microenvironments to a greater extent that the total numbers of receptors on the cell surface.